Wake up, Russia! Political activism and the reanimation of agency. Issue 5 (October 2016) - Mason, Jessica
Abstract : When protest movements do not achieve policy outcomes, they are often considered failures. But as I learned while working with feminist and pro‐LGBT activists in Moscow's radical left, becoming a political activist may in itself be an important form of resistance to overwhelming and demoralizing power structures. During the mass anti‐Putin protests of 2011–2012, which were widely experienced as an awakening of political subjectivities, to talk with activists about what constituted "politics" was to talk about the possibility of agency in the face of what often appears to be overwhelming constraint. Activism can thus be as much a form of subjectivity work as a means of changing public policy.